The brain of the North American cheetah-like cat Miracinonyx trumani - Figueirido-Castillo, Francisco Borja; Pérez-Ramos, Alejandro; Hotchner, Anthony; Lovelace, David M.; Pastor-Vázquez, Juan Francisco; Palmqvist-Barrena, Carlos Paul (Cell Press, 2022)
The cheetah Acinonyx jubatus, the fastest living land mammal, is an atypical member of the family Felidae. The extinct feline Miracinonyx trumani, known as the North American cheetah, is thought to have convergently evolved with Acinonyx to pursue fast and open-country prey across prairies and steppe environments of the North American Pleistocene. The brain of Acinonyx is unique among the living felids, but it is unknown whether the brain of the extinct M. trumani is convergent to that of Acinonyx. Here, we investigate the brain of M. trumani from a cranium endocast, using a comparative sample of other big cats. We demonstrate that the brain of M. trumani was different from that of the living A. jubatus. Indeed, its brain shows a unique combination of traits among living cats. This suggests that the case of extreme convergence between Miracinonyx and its living Old World vicar should be reconsidered.
Keywords: Craneología; Guepardos; Ecomorfología; Miracinonyx trumani; Molde endocraneal